Upaya Meningkatkan Kecerdasan Verbal Linguistik AnakMelalui Media Gambar Seri Pada Anak Kelompok A TK Pertiwi Sidowarno II Wonosari Klaten Tahun Ajaran 2014/ 2015 - Suciati, Resti Ana, Drs. Ilham Sunaryo, M.Pd AUD (2015)
Develop verbal intelligence linguistics teacher should use the media interest, so that cildren are more interestedin learning. One medium that can be used is the media image series, the media image is a series of images that contain a storyline that is arranged in a sequence. in the use of media image series, children can see the picture interesting and colorful. The purpose of the study was to improve verbal linguistic intelligence of children throught the medium of drawing the series on a group In Kindergarten Pertiwi Sidowarno II Of Wonosari Klaten Academic Year 2014/2015. This study used research method class. Subjec research and informants in this study were teachers protege funds methods of data collection is done throught observation, fields note, and documentation. Comparative analysis techniquee that compares the ability of children of research results with indicators of achievement or performance. The study states that by using the media image throught a series of story-telling method can improve verbal linguistic intelligence children of a group In Kindergarten Pertiwi Sidowarno II Of Wonosari Klaten Academic Year 2014/2015. The increase in the average percentage of verbal linguistic intelligence of the child beforethe procedure untul the second cycle of the before cycle 43,17%,first cycle 61,07% and the cycle II 83,52%. The conclusion of this study is a increase of the verbal linguistic intelligence by using media image of story tellingseries at children of a group In Kindergarten Pertiwi Sidowarno II Of Wonosari Klaten Academic Year 2014/2015.